SPATIAL INFLUENCE ON HUMAN BEHAVIOR IN OPEN SPACE USING THE ENTROPY METHOD: A CASE STUDY OF CAMPUS COMMUNITIES IN HANGZHOU CITY, CHINA - J. R. Shi; X. M. Zhao; H. Liu; K. Hokao; Z. Wang; J. Ge (Lowland Technology International, 2011)
The rapid urbanization of Chinese cities has been resulting to the degradation of urban residential environments. As a representative of green areas, residential open spaces play key roles to balance the needs for both conservation and development. Traditional ways to observe resident’s behavior mode only by calculating the absolute population count is not perfect. In order to achieve the goal of public benefits, this study attempts to develop traditional behavior approaches to establish an unconventional determinant factor to enable the examination of temporal regulation, spatial distribution and activity category of residents’ behavior through the Behavior Entropy Index (BEI). Through this study, the author hopes to provide recommendations to interrelate the local view into planning process. The data was collected in 6 different residential areas and 4 campuses in Hangzhou. In sum, the result obtained from the study aiming to not only satisfy residents’ desire of the improvement of open space but also bring to professional’s attention by examining the diversity of user’s behavior in the context of residential open space utilization and finding out physical factors which influence their satisfaction and behavior. The samples can be hopefully extended to reasonably represent the overall situation of Yangtze River Delta and provide a valuable reference for other regions of China.